Metagenomic shotgun sequencing and metabolomic profiling identify specific human gut microbiota associated with diabetic retinopathy in patients with type 2 diabetes - Li, Lihua; Yang, Kaibo; Li, Cong; Zhang, Han; Yu, Honghua; Chen, Kang; Yang, Xiaohong; Liu, Lei (Frontiers in Immunology, 2022)
Background: Diabetic retinopathy (DR) is a common microvascular complication of diabetes mellitus (DM), and is one of the leading causes of blindness among DM patients. However, the molecular mechanism involving DR remains unclear. Methods: A case-control study with age-, sex-, and duration-matched diabetic patients and controls was conducted, which included 15 type 2 DM (T2DM) patients with DR and 15 T2DM patients without DR. Shotgun sequencing and non-targeted metabolomics profiling analyses of fecal samples were performed, and comprehensive bioinformatics analyses were conducted. Results: Using metagenomic analyses, we identified 293,460 unique genes in the non-DR group, while that in the DR group was 283,235, and the number of overlapping genes was 1,237,914. Regarding phylum levels, Actinobacteria decreased but Bacteroidetes increased in the DR group, when compared with the control group. Regarding genus levels, Bifidobacterium and Lactobacillus decreased. Cellular processes, environmental information processes, and metabolism-related pathways were found at higher levels in the gut microbiome of DR patients. Using metabolomics analyses, we found 116 differentially-expressed metabolites with a positive ion model, and 168 differentially-expressed metabolites with a negative ion model, between the two groups. Kyoto Encyclopedia of Genes and Genomes annotation revealed four pathways with different levels between DR and diabetic controls, namely, cellular processes, environmental information processes, and metabolism-related pathways. Moreover, lysine biosynthesis and lysine degradation were enriched using a positive model, but histidine metabolism and β-alanine metabolism were enriched using a negative model. Conclusions: Together, the metagenomic profiles of DR patients indicated different gut microbiota compositions and characteristic fecal metabolic phenotypes in DR patients. Our findings of microbial pathways therefore provided potential etiological and therapeutic targets for DR patients.